The Body of Terror: The Evil Genius in the Silent House [el Cuerpo del Terror: El Genio Maligno en la Casa Muda] - Hermosilla-Órdenez, E (Pontificia Universidad Catolica de Chile 1, 2020)
This paper investigates the nature of the ghost and terror into philosophical thought, and how it allows us to reconsider, in the field of epistemology, the experience of terror in the perception, understanding and knowledge about reality. This analysis is developed, firstly, by means of the recovering of the evil genius figure mentioned in the Metaphysical Meditations by Rene Descartes, which provides a key to reconsider terror as an element present in the conformation of subjectivity. Besides that, it is based on the considerations on Jacques Derrida s cinema as a device for the production of spectra, meanwhile it allows us to understand the figure of the ghost as that which disrupts and alters the reality. Both lines of study converge in the analysis of the Uruguayan horror film The Silent House, directed by Gustavo Hernández, which opens the possibility of appreciating how terror is a bodily experience that allows the subject to access a new understanding of himself and his world. © Instituto de Estética - Pontificia Universidad Católica de Chile